Coding and Cryptology Third International Workshop, IWCC 2011, Qingdao, China, May 30-June 3, 2011. Proceedings - Chee, Yeow Meng.; Guo, Zhenbo; Ling, San.; Shao, Fengjing; Tang, Yuansheng; Wang, Huaxiong; Xing, Chaoping; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the Third International Workshop on Coding and Cryptology, IWCC 2011, held in Qingdao, China, May 30-June 3, 2011. The 19 revised full technical papers are contributed by the invited speakers of the workshop. The papers were carefully reviewed and cover a broad range of foundational and methodological as well as applicative issues in coding and cryptology, as well as related areas such as combinatorics.
Keywords: Computer science; Computer Communication Networks; Data encryption (Computer science).; Coding theory; Computational complexity; Computer Science; Coding and Information Theory; Data Encryption; Discrete Mathematics in Computer Science; Computer Communication Networks